Family Law Counselling as an Effort to Prevent Divorce in Terong Village, Dlingo District, Bantul Regency - Dakum, Dakum; Febrian Prastia, Alifio; Ridho Akhmad, Fahreza; Fauzan Ahdani, Prabu (Universitas Muhammadiyah Magelang, 2025)
The high divorce rate in Indonesia indicates the need to strengthen family resilience starting from the grassroots level. A lack of understanding regarding the essence of marriage, as well as the rights and obligations of husband and wife, often triggers household breakdown. This community service activity aims to provide family law education as a preventive measure against divorce in Dusun Terong, Terong Village, Dlingo District, Bantul Regency. The implementation method was carried out through legal counseling using a participatory approach and interactive discussions involving the community and local community leaders. The materials presented covered the Marriage Law, household conflict management, and dispute resolution procedures. The results indicated an increase in the partners' understanding regarding the legal consequences of divorce and the importance of deliberation within the family. Participants showed high enthusiasm and committed to making divorce the last resort (ultima ratio). It is concluded that increasing legal literacy through a sociological-religious approach is effective in building legal understanding and strengthening family resilience in Dusun Terong.